The non-linear risk of mortality by income level in a healthy population: US National Health and Nutrition Examination Survey mortality follow-up cohort, 1988-2001 - Coull Brent; Berkman Lisa F; Rehkopf David H; Krieger Nancy (BMC, 2008)
Abstract Background An examination of where in the income distribution income is most strongly associated with risk of mortality will provide guidance for identifying the most critical pathways underlying the connections between income and mortality, and may help to inform public health interventions to reduce socioeconomic disparities. Prior studies have suggested stronger associations at the lower end of the income distribution, but these studies did not have detailed categories of income, were unable to exclude individuals whose declining health may affect their income and did not use methods to determine exact threshold points of non-linearity. The purpose of this study is to describe the non-linear risks of all-cause and cause-specific mortality across the income distribution. Methods We examined potential non-linear risk of mortality by family income level in a population that had not retired early, changed jobs, or changed to part-time work due to health reasons, in order to minimize the effects of illness on income. We used data from the US National Health and Nutrition Examination Survey (1988-1994), among individuals age 18-64 at baseline, with mortality follow-up to the year 2001 (ages 25-77 at the end of follow-up, 106 037 person-years of time at risk). Differential risk of mortality was examined using proportional hazard models with penalized regression splines in order to allow for non-linear associations between mortality risk and income, controlling for age, race/ethnicity, marital status, level of educational attainment and occupational category. Results We observed significant non-linear risks of all-cause mortality, as well as for certain specific causes of death at different levels of income. Typically, risk of mortality decreased with increasing income levels only among persons whose family income was below the median; above this level, there was little decreasing risk of mortality with higher levels of income. There was also some variation in mortality risk at different levels of income by cause and gender. Conclusion The majority of the income associated mortality risk in individuals between the ages of 18-77 in the United States is among the population whose family income is below the median (equal to $20,190 in 1991, 3.2 times the poverty level). Efforts to decrease socioeconomic disparities may have the greatest impact if focused on this population.